Surface nanostructuring of Ti-6Al-4V alloy through ultrasonic shot peening - Kumar S.; Chattopadhyay K.; Singh S.R.; Singh V. (My University, 2025)
Solution treated samples of titanium alloy Ti-6Al-4V were subjected to ultrasonic shot peening (USSP) for different durations of 5, 15, and 30 minutes with hard steel balls of 3 mm diameter and examined for modification of microstructure, surface roughness and hardness profile. Based on microhardness profile a nanostructured layer of approximately 100 μm thickness resulted from the USSP. The shot peened surfaces were examined also by XRD for phase transformation, if any, resulting from USSP. Grain refinement was observed to nano scale due to USSP without any phase transformation. However, surface cracking was observed in the sample subjected to longer duration of 30 minutes and surface roughness was increased with duration of USSP. Microhardness of the 30 minutes shot peened surface was increased by ∼34%, however, the increased hardness level was reduced by ∼14%, following stress relieving treatment (400°C-1 h). The results are discussed in terms of the processes of grain refinement through USSP. Copyright © 2017 Inderscience Enterprises Ltd.